Odpowiedź
6. jednomiany: 4a, -5xyz, 9x²y³, -1,5ax
6. wielomiany: 12a - 5b, 3x - 5y - 6z
7a. b
[tex](2a - 3b) + (-2a + 4b) =\\\\2a - 3b - 2a + 4b =\\\\2a - 2a - 3b + 4b =\\\\0 + 1 \cdot b \: = \: b[/tex]
7b. -3x - 2y - 1
[tex](x - 2) - (4x + 2y - 1) =\\\\x - 2 - 4x - 2y + 1 =\\\\x - 4x - 2y - 2 + 1 = -3x - 2y - 1[/tex]
7c. 3a + 12b - 6
[tex]3(a + 4b - 2) =\\\\3 \cdot a + 3 \cdot 4 \cdot b - 3 \cdot 2 = 3a + 12b - 6[/tex]
Szczegółowe wyjaśnienie
W jednomianie nie ma dodawania. A jeśli jest znak minus, to przed nim nic nie ma.